If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) = -1.2 Reorder the terms: 3(-4 + x) = -1.2 (-4 * 3 + x * 3) = -1.2 (-12 + 3x) = -1.2 Solving -12 + 3x = -1.2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 3x = -1.2 + 12 Combine like terms: -12 + 12 = 0 0 + 3x = -1.2 + 12 3x = -1.2 + 12 Combine like terms: -1.2 + 12 = 10.8 3x = 10.8 Divide each side by '3'. x = 3.6 Simplifying x = 3.6
| 100x-29=42671 | | 1/4x-1/8x=3-1/16x | | 60x=100 | | 7(a+2)=34.3 | | x*3=18 | | 0.25y-3.5=0.15y+1-0.8y | | 100x-29=100(426.71) | | -2/3x+2=6 | | 3(-2x+1)-4(-x)=-x+19 | | 3(-2x+1)-4(-x)=x+19 | | 3t+2(t+1)+7t+6=-16 | | 3x+6=3x-12 | | 7m-25=-32+6m | | z-42=-41 | | 20=5c-3 | | 2(x-3)=3x+3 | | x-0.6=9.36 | | 7e-9=19.7 | | ax=5a | | n^3-n=7n^2-5 | | n^3-n=7n^2-5 | | 3x=b/a | | 17(3)= | | 7p=50.4 | | 8x+14=12x-22 | | 3(x+5)+4(x-3)-6x=4 | | 17m=170 | | (x)(x+8)=96 | | 120-4x=40 | | 12-5x=-58 | | 7+9x=97 | | A(6a-3)= |